Advertising, Public Relations and Social Marketing: shaping behaviour towards sustainable consumption - Muratovski, G (Routledge, 2013)
As the world struggles to sustain mass consumption as a lifestyle of choice, the need for sustainable behaviour becomes increasingly evident. Even though there are already a number of technical and legislative solutions underway, we still need to work on changing our consumption habits. This calls for social marketing strategies that can lead to promotion and acceptance of sustainable behaviour on a global scale. The problem, however, is that social marketing for sustainability that dominates the media today is ineffective and even counterproductive. In this study, I will examine what drives consumerism, and argue that sustainable consumption could be promoted as an alternative lifestyle, based on the same strategies that have successfully established mass consumption as a way of life. Countering the claims made for traditional social marketing, I will suggest that appealing to people’s innermost desires in the same way commercial marketing does, is in fact a more effective means of behaviour change than the negative information campaigns that are prevalent today. This calls for a different type of social marketing—one based on positive appeals related to subjective wellbeing and self-fulfilment, and not on scare tactics and dull educational campaigns.
Keywords: Advertising; Marketing; Public Relations; Sustainability; Behaviour; Change